Entre Josefas, rezas e rodas : a práxis do cuidado em saúde e o empoderamento da mulher quilombola - Santos, Maria Taires dos (2022)
Quilombola women play an important role in maintaining the cultural traditions of their territories. In Sergipe, Dona Zefa da Guia and Dona Josefa do Sítio Alto are the guardians of traditional health care knowledge, also recognized for their important role in the political, social and cultural organization of their communities. Among prayers, dances, songs, medicinal plants, childbirth, conservation of native seeds, and other practices and knowledge based on Afro-Brazilian civilization values, including ancestry, they have promoted an important process of individual and collective empowerment of their communities. Knowledge and practices that survive even amidst the hegemony of the biomedical paradigm, which strongly obeys the logic imposed by the capitalist economic system of production. This paper aims to analyze how the traditional knowledge of health care empowers quilombola women. Through the oral life history research method, qualitative approach and data analysis based on interpretative anthropology, we conducted the research with Dona Zefa da Guia and Dona Josefa from Sítio Alto. We conclude that the traditional health care knowledge and practices are knowledge conceived and articulated by the Josefas and constitute means of reaffirming the cultural identity of Serra da Guia and Sítio Alto. They establish conditions of political and cultural resistance for the promotion of healing, well-being and health of the people of these communities. This knowledge and practice of health care consists of systematized action and reflection, which we call the praxis of quilombola health care, and shows itself capable of fostering collective organizational processes. The quilombola health care practice of Dona Zefa da Guia and Dona Josefa do Sítio Alto is based on ancestry, spirituality, the harmonious relationship with the environment, and the transforming force of love, and that together, in an articulated manner, is defined as a fundamental tool for the critical awareness in the empowerment process of both, as well as of their respective communities.